The Impact of Youtube Animated Videos on Students’ Motivation and Vocabulary Development in Learning English at SDN 26 Palu - Jafar, Desi M; Usman, Sriati; Marhum, Mochtar; Sadilia, Sukmawati; Putri, Dwi (Journal of English Language and Education, 2025)
This study investigates the impact of YouTube animated videos on students’ motivation and vocabulary development in learning English at SDN 26 Palu. In recent years, technology integration in language education has become crucial for enhancing young learners’ engagement and comprehension. However, few studies have examined the specific effects of YouTube animated videos within Indonesian public elementary school contexts. This study employed a mixed-methods design combining quantitative and qualitative approaches. A pre-experimental one-group pre-test and post-test design measured vocabulary improvement, while interviews and classroom observations explored students’ motivation. The participants consisted of 15 sixth-grade students who took part in six meetings over two weeks. The findings revealed that the use of YouTube animated videos significantly enhanced students’ vocabulary mastery and motivation in learning English. Quantitative data showed a mean increase of 10.2 points from pre-test to post-test, while qualitative data indicated that students found the videos engaging and enjoyable. It is concluded that YouTube animated videos are effective and accessible media for improving English vocabulary and sustaining motivation among elementary learners.